Reasons for living and depressive symptomatology in young adults with and without suicide attempts: a moderated mediation approach - Brás, Marta; Martins, Cátia; Nunes, Cristina; Jesus, Saul Neves; Madeira, Ana Rita; Carmo, Cláudia (Frontiers in Psychiatry, 2025)
IntroductionSuicide is a public health problem worldwide, being the fourth leading cause of death in young adult population (15-29 years). Therefore, it is important to identify its risk and protective factors, and how they interact to develop more effective interventions. The present study aims to analyze the relation between depressive symptoms, hopelessness (risk factors) with reasons for living (protective factors) and suicidal ideation in young adults with and without previous suicide attempts.MethodsA sample of 845 Portuguese young adults answered an online form which assessed suicidal ideation, hopelessness, depressive symptoms, and reasons for living. Mean comparisons, correlations, and moderated mediation analysis were computed.ResultsIndividuals with a history of suicide attempt showed higher mean levels in risk factors, compared to individuals without suicide attempt. When no history of suicide attempt was present, ideation was positively and significantly correlated to depression and hopelessness, and negatively correlated to the reasons for living. Higher levels of depressive symptomatology predict lower levels of reasons for living. Mediation and moderation relations were assessed in a model and the history of suicide attempts showed a relevant role.ConclusionsThe evidence found in this study reinforce that reasons for living may play a preponderant role in suicidal ideation, that is as a negative mediator and therefore it can act as a protective factor.